THE LINK BETWEEN THE ART AND THE CULTURE OF ALGERIAN SOCIETY - Boulakroune Abderrahmane; Benazza Ahmed (International Journal of Innovative Technologies in Social Science, 2025)
The arts in Algeria have existed since the existence of humankind, occupying and influencing people as both a material and moral medium that surrounds them and within which they live. Practicing art became a unique style that distinguishes individuals from other environments where arts originated and flourished. It is used to re-educate societal emotions and instill behaviors of beauty. The forms of artistic representation and expression have diversified according to the culture and environment of Algerian society. From the design of stone hunting tools to mural paintings, to dancing as an expression of emotions, and performances that descended from religious rituals and mass ceremonies to ward off evil spirits, art has been an integral part of human experience. At other times, people celebrate by singing and chanting during war and peace, just like people worldwide, reflecting their inner emotions, whether negative or positive. Furthermore, the Algerian individual has mastered drawing strength from unity and adhering to the principles of social cohesion derived from the actual conditions and fundamental elements of Algerian society’s culture across various historical periods. The cultural pattern, imbued with adherence to values, customs, and traditions, has played a significant role in shaping the Algerian audience’s taste for artistic works. These works, in turn, are governed by principles that enable artists to achieve aesthetic, utilitarian, and industrial goals, or simply provide pleasure and entertainment. Sometimes, they even cater to psychological desires, including erotic stimulation, considering that the artist seeks to employ their imagination and freedom, which govern their behavior and orientation. Art narrates the history of humankind and provides us with cultural knowledge, as it intersects with various aspects of life and the prevailing sciences of each era. It offers different perspectives from multiple angles, remaining both enduring and renewable due to its intrinsic nature. Art is a refined creative activity, constantly evolving and deeply rooted, as it stems from the human spirit. Thus, artistic beauty is the highest form of beauty, whose significance is undeniable due to its rank. It reflects the level of human progress in a specific society within spatial and temporal boundaries and, beyond that, serves as an expressive language linked to the spirit of the nation.